2014
DOI: 10.5051/jpis.2014.44.4.184
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of computer-aided template-guided oral implant placement: a prospective clinical study

Abstract: PurposeThe aim of the present study was to evaluate the in vivo accuracy of flapless, computer-aided implant placement by comparing the three-dimensional (3D) position of planned and placed implants through an analysis of linear and angular deviations.MethodsImplant position was virtually planned using 3D planning software based on the functional and aesthetic requirements of the final restorations. Computer-aided design/computer-assisted manufacture technology was used to transfer the virtual plan to the surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 27 publications
(35 reference statements)
2
40
1
3
Order By: Relevance
“…It has been shown that the use of a surgical guide reduces inaccuracies in the transfer of Clin Implant Dent Relat Res. [9][10][11][12] Other factors influencing accuracy were the type of edentulous space, 13 the nature of the remaining teeth, 14,15 the implant system used, 16 and the surgical approach (flap vs flapless 17 or delayed vs immediate placement 18 ). [1][2][3][4] The individual steps of the planning process must be as precise as possible for the sum of the errors to ultimately yield a clinically tolerable discrepancy between the actual and planned implant positions.…”
Section: B Ac Kgr Oundmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the use of a surgical guide reduces inaccuracies in the transfer of Clin Implant Dent Relat Res. [9][10][11][12] Other factors influencing accuracy were the type of edentulous space, 13 the nature of the remaining teeth, 14,15 the implant system used, 16 and the surgical approach (flap vs flapless 17 or delayed vs immediate placement 18 ). [1][2][3][4] The individual steps of the planning process must be as precise as possible for the sum of the errors to ultimately yield a clinically tolerable discrepancy between the actual and planned implant positions.…”
Section: B Ac Kgr Oundmentioning
confidence: 99%
“…5 Some studies have examined the influence of the manufacturing process of a template on the accuracy achieved, [6][7][8] while others concerned themselves with the influence of different types of template support. [9][10][11][12] Other factors influencing accuracy were the type of edentulous space, 13 the nature of the remaining teeth, 14,15 the implant system used, 16 and the surgical approach (flap vs flapless 17 or delayed vs immediate placement 18 ). Some studies also examined how the accuracy of template-supported implant placement performed in general, compared with free-handed placement.…”
Section: B Ac Kgr Oundmentioning
confidence: 99%
“…We decided to install five Bredent implants, diameter of 4 mm and a length of 12 mm, 2 implants on the left side at the positions #36 and #37 and 3 implants on the right side at the positions #45, #46 and #47. Romexis software executed a virtual Also some other shortcomings, such as surgical guide shape, length of metal sleeve and surgical drill, template supporting problem, can be found in the literature 13,[15][16][17][18] .…”
Section: Figure 1 Orthopantomogrammentioning
confidence: 99%
“…41 Mevcut bu zorlukların giderilmesinde CAD/CAM sistemleri ile kombine olarak kullanılan konik ışınlı bilgisayarlı tomografi/bilgisayarlı tomografi (KIBT/BT) tekniği günümüzde sıklıkla kullanılmaktadır. 19,25,27,42,43 Bu tekniklerden biri olan stereolitografi (SLA) yöntemi kullanılarak lazer polimeri-zasyon işlemi ile anatomik modelden cerrahi kılavuz elde edilebilmektedir. 13,19,20,27 Stereolitografi, lazer ışını kullanılarak ultraviole ışına hassas, sıvı rezinin seçici olarak sertleşerek model elde etme işlemidir.…”
Section: Geleneksel Cerrahi Kılavuzlarunclassified